Cross-sectional study of vaccine coverage among children aged 1 to 24 months in Opuwo District, Kunene region, Namibia - Ligola S. M. Akwenye; Junxian Ou; Chengsong Wan; Wei Zhao; Zhixin Fang; Qiwei Zhang (BMC Public Health)
Abstract Vaccination has been shown to be one of the most cost-effective health interventions worldwide, successfully preventing a number of serious childhood diseases. A retrospective analysis of vaccine coverage among children aged 1 to 24 months in the Opuwo district of the Kunene region in Namibia was conducted using the District Health Information System, along with a questionnaire administered to caretakers of children seeking healthcare services at randomly selected health facilities. In our study, we analyzed the children’s immunization status regarding the oral/inactivated polio vaccine, pneumococcal vaccine, rotavirus vaccine, measles and rubella vaccine and a pentavalent vaccine that prevents five types of diseases, including diphtheria, pertussis, tetanus, hepatitis B, and haemophilus influenzae type b. Results showed that during 2019–2020, at least 57.2% of the antigens reached the recommended coverage of over 80% in Opuwo District. Additionally, 62.5% of health facilities met the district target coverage of a minimum of 85% for four or more antigens. In correlation analyses using bivariate and linear regression tests, factors such as educational level (P < 0.001), parental occupation (P = 0.001), child’s place of birth (P < 0.001), antenatal care services attendance (P = 0.036) and birth order (P = 0.017) were significantly associated with immunization status of surveyed children. No significant association was found between male and female (P = 0.094), the main source of information (P = 0.056), place of residence (P = 0.083) and immunization status, respectively. Other factors included residing far from the health facilities, lack of funds to cater for transport as well lack of knowledge as to when the child was due for immunization were found to be reasons of unvaccinated or partially immunized. Such factors contributing to immunization rate of children should be highlighted and policies to educate the caretaker of children should be considered and enforced, in order to further increase immunization rate of children in relatively less developed areas.